Psychology in Education and Health- Proceedings of the II Leipzig-Évora Scientific Meeting in Psychology - Candeias, Adelinda (2019)
This ebook contains several papers on the application applied psychology in education, health and well-being, personality,family interactions and emotional and epistemological development.The aim of this volume is to inform the scientific community on the research on Psychology mainly made at Évora and Leipzig Universities, but also in other contexts like Mexico or Brazil.